Improving students’ cognitive process in biology using concept mapping and cooperative mastery learning strategies - Dieudonné Mutangana; Adrian Mwesigye; Emmanuel Bizimana (International Journal of Evaluation and Research in Education (IJERE), 2022)
Students’ performance in biology in Rwanda National Examinations has been reported to be unsatisfactory. This demands teachers to shift to methods that enable students to acquire meaningful learning. In an attempt to cope with this situation, the effects of concept mapping (CM) and cooperative mastery learning (CML) on the cognitive process in biology among lower secondary school students in Nyamagabe district, Rwanda was investigated. A quasi-experimental non-equivalent pre-test, post-test control group design was applied to a sample of 449 senior secondary school two (SS2) students (224 males and 225 females) drawn from seven co-educational secondary schools purposively selected from 46 schools. The students were in CM (n=151), CML (n=144) and conventional teaching method (CTM) (n=154) groups. The biology Achievement Test with a reliability of 0.82 obtained from the Kuder Richardson (KR-21) formula was used to collect data. Analysis of Covariance and Bonferroni test were applied for data analysis. Findings revealed that CM and CML groups scored better in all cognitive domains tested than the CTM group. A statistically significant difference between CM and CML was observed in favor of the CM. Based on the findings, it was concluded that the CM and CML are capable of improving secondary school students’ mastery of the content taught at all levels of cognition. Therefore, learning with CM and CML could be a viable option for teachers for addressing attainment issues in biology.